(untitled) (Journal of the College of Basic Education, 2022)
The scale of perception among Arab and Islamic peoples of the danger of the Great Middle East project is very high, but the ignorance and poverty imposed on these peoples, as well as the regional and internal wars, ethnic and sectarian ones, have had an effect on weakening the Arab and Islamic nation. This project has gone through several stages over more than a century of Time and the approval of the Allied countries in this project, especially Britain, the United States of America, France, and Russia, and then the emergence of the Zionist entity, that what Bernard Lewis brought is the final division of the Zionist-American project, which has already begun to be implemented on the ground by creating wars and internal crises in some of those countries to redraw a map The peoples of the region . The theory of geopolitical deterrence came to confront the Greater Middle East project and restore the cohesion of the ethnically, religiously and sectarian torn countries, and make those countries one country with high capabilities in economic, political and military terms, as well as building a political, military and economic decision-making center for it called the heart region, that the ancient and modern colonialism was an attempt. To present logical solutions in how to divide the Middle East into small cantons in order to easily control them without losses or reduce them to a minimum, with the blessing and satisfaction of their people, to get rid of the stage of religious, ethnic and sectarian wars, which were and are still one of the weapons of implementing the Greater Middle East project . The theory of geopolitical deterrence is the shield that works to thwart the Greater Middle East project if the appropriate conditions are provided for that. The implementation of this theory on the ground can only be achieved by the efforts of these peoples, their awareness and belief in unity, strength and common interest, and their awareness of the seriousness of the Greater Middle East project. The problem / is it possible to divert the path of force by building a new core area ? Hypothesis / 1- It is possible to build alliances that would enable them to build a Middle Eastern force to control it. 2-Ensuring the destruction of the Greater Middle East project through the military, political and economic control of the new core region . The research included several topics, namely :- The first topic / The Greater Middle East Project, its goals and geopolitical impact on the Arab world. The second topic / Bernard Lewis’ theory of the Greater Middle East project and the signs of implementation . The third topic / geopolitical deterrence theory.